Product development of sola plant (Aeschynomene aspera Linn.) for economic benefit of the community - Muchjajib, Udomlaksana; Sirikesorn, Laongsri; Sinpho, Suwanchai; Nittayapongchai, Nanthapad; Suphap, Pinthip; Muchjajib, Surachai (RMUTSB ACADEMIC JOURNAL, 2014)
Sola plant (Aeschynomene aspera Linn.) is an aquatic broad-leaved weed in deep water rice paddy fields. It is native to South and Southeast Asia. Its cortex pith is an excellent raw material for several types of handicrafts. The handicraft product from sola plant in Thailand is paper-pith flower e.g. jasmine, sunflower, chrysanthemum, gerbera, red ginger, poppy and lotus. This research is aimed at establishing models with various diversity of products from stem pith and stem bark of sola plant to promote economic benefit to the community enterprise via women%s OTOP (one tumbon one product) group in the central provinces: Ayutthaya, Angthong, Suphanburi, Nonthaburi and Pathumthani. The peeling machine was developed to help reduce time of peeling. It took a day to finish 1000 g of sola stem peeling process. The scores of customer satisfaction on the new models ranged from 4.05 to 4.88 regarding a scale of one to five with a score of one representing "very dissatisfied" and five representing "very satisfied".